PERAN UNITED NATIONS DEVELOPMENT PROGRAMME INDONESIA DALAM MENGIMPLEMENTASIKAN DIFUSI INOVASI AGENDA SUSTAINABLE DEVELOPMENT GOALS UNTUK MEMBANGUN KESADARAN PEMUDA MENGENAI MASALAH SAMPAH PLASTIK - Joe Harrianto Setiawan; Cintia Caroline (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
The United Nations Development Program (UNDP) in Indonesia carrying out the mandate contained in the global development agenda / Sustainable Development Goals (SDG). Long-term development in Indonesia is threatened by environmental degradation and climate change shown by the status as one of the biggest producers of greenhouse gas emissions and plastic waste in the world. SDG is a diffusion of innovation activity is targeting the role of youth in its process towards sustainable development. By using the main theory Diffusion of Innovation and with descriptive qualitative research methods, the result has shown that the diffusion of innovation UNDP is not so complicated, but still has difficulty in including the agent of change, therefore it needs a direct approach that is friendly and easy for the youth to understand. UNDP Indonesia diffuses the innovations through internet and events/programs through the contribution of the agent of change.